2022
DOI: 10.3390/ijerph19052821
|View full text |Cite
|
Sign up to set email alerts
|

Monochorionic Twins and the Early Mother-Infant Relationship: An Exploratory Observational Study of Mother-Infant Interaction in the Post-Partum Period

Abstract: The extraordinary increase in twin rates and specifically monochorionic twin pregnancies represents a major public health issue due to the associated increased risks for the mother, the child and their relationship. The aim of the present study was to examine the quality of mothers’ behaviour during mother–infant interaction in the early postpartum period by comparing mothers of twins and mothers of singletons during face-to-face interaction with their infants. Demographic and clinical information was collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Bonding is also linked with maternal mental health (Tichelman et al 2019 ) and stress (Lutkiewicz et al 2020 ). Prior work has found that mothers of twins often express sadness and guilt over insufficient time to bond with both babies (Wenze et al 2020 ), and behavioral observation suggests that, compared to mothers of singletons, mothers of twins demonstrate lower sensitivity and more distant behaviors when interacting with their babies (Ionio et al 2022 ). No research of which we are aware has directly measured self-reported maternal-infant bonding in mothers of multiples versus mothers of singletons.…”
mentioning
confidence: 99%
“…Bonding is also linked with maternal mental health (Tichelman et al 2019 ) and stress (Lutkiewicz et al 2020 ). Prior work has found that mothers of twins often express sadness and guilt over insufficient time to bond with both babies (Wenze et al 2020 ), and behavioral observation suggests that, compared to mothers of singletons, mothers of twins demonstrate lower sensitivity and more distant behaviors when interacting with their babies (Ionio et al 2022 ). No research of which we are aware has directly measured self-reported maternal-infant bonding in mothers of multiples versus mothers of singletons.…”
mentioning
confidence: 99%
“…Thus, one might assume that mothers of dizygotic twins are more likely to report differential maternal-infant bonding. On the other hand, monozygotic (and especially monochorionic) pregnancies have been found to entail higher levels of maternal stress, anxiety, and depression than dizygotic pregnancies, due to signif-icantly higher medical risk, and these symptoms can put the dyad at risk for poor maternal-infant bonding (for a review, see Ionio et al, 2022). Thus, it is unclear whether zygosity might be linked with potential maternal-infant bonding discrepancies.…”
Section: What Factors Might Be Associated With Differential Maternal-...mentioning
confidence: 99%
“…Prior work suggests that self‐reported maternal‐infant bonding is, on average, lower in mothers of twins than in mothers of singletons (Wenze et al., 2023), and behavioral observation has found that mothers of twins demonstrate lower sensitivity and more distant behaviors while interacting with their babies (Ionio et al., 2022). Mothers of twins commonly report feelings of loss, grief, and guilt over insufficient time to bond individually with both of their babies (Gowling et al., 2021; Holditch‐Davis et al., 1999; Wenze et al., 2020).…”
Section: Introductionmentioning
confidence: 99%